Searching for the erosion of empathy in medical undergraduate students: a longitudinal study. Issue 12 (31st December 2020) - Blanco, José Manuel; Caballero, Fernando; Álvarez, Santiago; Plans, Mercedes; Monge, Diana
Abstract : Objective: To analyse the trajectory of empathy throughout the degree programme of medicine in a Spanish school of medicine. Design: Longitudinal, prospective 5-year study, between October 2014 and June 2019. Setting: Students from a Spanish university of medicine. Participants: Two voluntary cohorts of undergraduate medical students from two different school years were invited to participate (n=135 (cohort 1, C1) and 106 (cohort 2, C2) per school year). Finally, a total number of 174 students (102 (C1, 71.6% women) and 72 (C2, 70.8% women) students, respectively) were monitored for 5 years. Each cohort was divided in two subcohorts of paired and unpaired students that were analysed to check possible social desirability bias. Primary outcome measure: The Jefferson Scale of Empathy (JSE). Results: The cohort of 102 students (C1) monitored between their first and fifth years of study (71.6% women) showed an improvement among paired women of 2.15 points in total JSE score (p=0.01) and 2.39 points in cognitive empathy (p=0.01); in the unpaired female cohort the increase was of 2.32 points (cognitive empathy) (p=0.02). The cohort of 72 students (C2) monitored between their second and sixth years of study (70.8% women) displayed a cognitive empathy increase of 2.32 points (p=0.04) in the paired group of women. There were no significant differences between paired and unpaired results for either cohort. Empathy scores among men did not decrease. Conclusions: The empathy of medical students at our school did not decline along grade years. In fact, it improved slightly, particularly cognitive empathy, among women. This paper contributes to enlarge data from Europe, where longitudinal studies are scarce. It supports the idea that there may be global geo-sociocultural differences; however, more studies comparing different school settings are needed.